CONDITIONS OF OBTAINING LOANS FROM THE PERSPECTIVE OF MANAGEMENT OF AGRICULTURAL FARMS AND MEDIUMSIZED AGRICULTURAL ENTERPRISES, THE EXAMPLE OF THE REPUBLIC OF SERBIA - Lutovac, Jelena; Veličković, Milinko; Zimonjić, Marijana (Economics of Agriculture, 2024)
A number of factors can affect getting a loan. The aim of the study was to determine the possible influence of the following factors: interest rate, loan repayment term, user participation, VAT lending possibilities, agricultural equipment as a pledge, simplicity of the lending procedure, minimum loan amount, adjustment of repayment and total score in the period 2022- 2024 on getting a loan. The application of the t-test revealed that there is a strong influence of all the mentioned factors on obtaining loans in agricultural holdings, that is, in the operations of medium-sized agricultural enterprises. The next conclusions would be that the mentioned factors affect the prediction of the interest rate in the business of agricultural farms (F=185.24, p<0.0005) but also in the business of medium-sized agricultural companies (F=106.51, p<0.0005) in the Republic of Serbia.